Exploring Identity and Self-Discovery in Modern Feminism - Dr. Ranjana Kumari (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper examines the critical role of identity and self-discovery within contemporary feminist thought and practice. It explores how modern feminism foregrounds individual and collective experiences in shaping personal identities, challenging traditional gender norms, and fostering empowerment. By analyzing diverse narratives and theoretical frameworks, the study highlights the intersectionality of identity factors such as race, class, sexuality, and culture in the ongoing journey of self-awareness and political agency. The paper argues that self-discovery is not only a personal endeavor but also a transformative process that underpins feminist activism and social change in the 21st century. Through this exploration, the research contributes to a deeper understanding of how identity formation drives feminist discourses and influences the evolving landscape of gender equality.
Keywords: Identity; Self-Discovery; Contemporary Feminism; Gender Norms; Intersectionality; Feminist Theory; Agency; Empowerment; Personal Transformation; Social Construction of Identity